2016
DOI: 10.1017/s1431927616009697
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy Investigation of Binder Saturation and Microstructural Defects in Functional Parts Made by Additive Manufacturing

Abstract: Metallic foams of ferromagnetic Ni-Mn-Ga Heusler alloy show an 8.7% magnetic field induced strain (MFIS) [1]. The large MFIS in foams are orders of magnitude higher compared to bulk polycrystalline Ni-Mn-Ga, revealing that porosity is responsible for the increase in MFIS. Additive manufacturing (AM) techniques such as powder-bed binder-jet technique, known as 3D printing, are suitable for producing near-net shaped parts with controlled porosity. AM is a relatively new method of engineering that produces near-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Preheating was required [97] E-PBF process resulted in better tensile properties than L-DED and L-PBF [97,122] PAD Pre-alloyed powder Linear superelasticity [123] Quasi-linear superelasticity with narrow hysteresis [123,124] WAAM Wire High hardness and tensile strength [125] Cu-Al-Ni L-PBF Elemental powders High aluminum content led to dendrites and high hardness [126] Cu-Al-Ni-Mn Gas atomized powder High relative density (>92%) achieved [127][128][129] Reversible martensitic transformation with the formation of β 1 '-martensite [127][128][129] Large strain recovery after unloading (up to 18%) [127] Strong distribution of pores produced by the L-PBF sample [127,128] Additional re-melting led to smaller grain size and yielded a deformability of 14% [129] Higher strength and improved plasticity was observed for both samples (Cu-Al-Ni-Mn and Cu-Al-Ni-Mn-Zr) [128][129][130] For the Cu-Al-Ni-Mn-Zr sample, Zr-rich phase was found to precipitate at the grain boundaries during the annealing process [130] Cu-Al-Ni-Mn-Zr Cu-Al-Ni-Ti Copper alloy with Ti addition had a high hardness of about 280 HV due to the grain refinement. The relative density exceeded 99% [131] Fe-Mn-Al-Ni Reversible martensitic transformation and pseudo-elastic effect [132] MSMA Ni-Mn-Ga 3D ink printing Ink with elemental powders Reversible martensitic transformation [133] Martensitic twins [134] Binder jetting Mechanically produced powder Martensitic twins and reversible martensitic transformation after post-processing [135,136] Binder jetting produced a complex-shaped porous Ni-Mn-Ga geometry with a reversible martensitic transformation [137][138][139] Sintering of Ni-Mn-Ga powder was shown to produce net-shaped porous structures…”
Section: Micro L-pbfmentioning
confidence: 99%
See 1 more Smart Citation
“…Preheating was required [97] E-PBF process resulted in better tensile properties than L-DED and L-PBF [97,122] PAD Pre-alloyed powder Linear superelasticity [123] Quasi-linear superelasticity with narrow hysteresis [123,124] WAAM Wire High hardness and tensile strength [125] Cu-Al-Ni L-PBF Elemental powders High aluminum content led to dendrites and high hardness [126] Cu-Al-Ni-Mn Gas atomized powder High relative density (>92%) achieved [127][128][129] Reversible martensitic transformation with the formation of β 1 '-martensite [127][128][129] Large strain recovery after unloading (up to 18%) [127] Strong distribution of pores produced by the L-PBF sample [127,128] Additional re-melting led to smaller grain size and yielded a deformability of 14% [129] Higher strength and improved plasticity was observed for both samples (Cu-Al-Ni-Mn and Cu-Al-Ni-Mn-Zr) [128][129][130] For the Cu-Al-Ni-Mn-Zr sample, Zr-rich phase was found to precipitate at the grain boundaries during the annealing process [130] Cu-Al-Ni-Mn-Zr Cu-Al-Ni-Ti Copper alloy with Ti addition had a high hardness of about 280 HV due to the grain refinement. The relative density exceeded 99% [131] Fe-Mn-Al-Ni Reversible martensitic transformation and pseudo-elastic effect [132] MSMA Ni-Mn-Ga 3D ink printing Ink with elemental powders Reversible martensitic transformation [133] Martensitic twins [134] Binder jetting Mechanically produced powder Martensitic twins and reversible martensitic transformation after post-processing [135,136] Binder jetting produced a complex-shaped porous Ni-Mn-Ga geometry with a reversible martensitic transformation [137][138][139] Sintering of Ni-Mn-Ga powder was shown to produce net-shaped porous structures…”
Section: Micro L-pbfmentioning
confidence: 99%
“…All the scientific literature available at the time focuses on the additive manufacturing of Ni-Mn-Ga-based MSMAs. The most common approaches on additive manufacturing of Ni-Mn-Ga have concentrated on 3D ink printing [133,134] and binder jetting [135][136][137][138][139][140]. However, also a few investigations into manufacturing of polycrystalline Ni-Mn-Ga using L-DED [141] and L-PBF [142][143][144][145][146] have recently been published.…”
Section: Additive Manufacturing Of Magnetic Shape Memory Alloysmentioning
confidence: 99%
“…Binder jetting additive manufacturing provides major benefits for obtaining NiMnGa components displaying magnetic shape memory effect (MSME) [1][2][3]. In the case of NiMnGa alloys it was proved that cast porous materials with bimodal pore-size distributions shows a magnetic field induced strain (MFIS) up to 8.7% [4].…”
mentioning
confidence: 99%
“…Lázpita et al showed that fine-grained and randomly textured Ni-Mn-Ga samples exhibit hardly any MFIS under an external magnetic field due to internal constraints on twin boundary motion [4]. Recently, there has been interest in manufacturing Ni-Mn-Ga systems containing a porous network over a completely dense polycrystalline sample in order to enhance the MFIS [5]. According to Müllner et al, the MFIS is highly diminished in solid polycrystalline Ni-Mn-Ga as the grain boundaries inhibit the movement of twin boundaries.…”
mentioning
confidence: 99%